Scanning acoustic microscopy investigation of frequency-dependent reflectance of acid- Etched human dentin using homotopic measurements - Misra, Anil S.; Spencer, Paulette; Katz, J. Lawrence; Marangos, Orestes (My University, 2011)
Composite restorations in modern restorative dentistry rely on the bond formed in the adhesive-infiltrated acid-etched dentin. The physical characteristics of etched dentin are, therefore, of paramount interest. However, characterization of the acid-etched zone in its natural state is fraught with problems stemming from a variety of sources including its narrow size, the presence of water, heterogeneity, and spatial scale dependency. We have developed a novel homotopic (same location) measurement methodology utilizing scanning acoustic microscopy (SAM). Homotopic measurements with SAM overcome the problems encountered by other characterization/ imaging methods. These measurements provide us with acoustic reflectance at the same location of both the pre- and postetched dentin in its natural state. We have applied this methodology for in vitro measurements on dentin samples. Fourier spectra from acid-etched dentin showed amplitude reduction and shifts of the central frequency that were location dependent. Through calibration, the acoustic reflectance of acidetched dentin was found to have complex and non-monotonic frequency dependence. These data suggest that acid-etching of dentin results in a near-surface graded layer of varying thickness and property gradations. The measurement methodology described in this paper can be applied to systematically characterize mechanical properties of heterogeneous soft layers and interfaces in biological materials. © 2011 IEEE.
Keywords: Acoustic measurements; Acoustics; Frequency measurement; Reflection; Substrates; Surface treatment